Agent Force Implementation in Modern CRM: A Mixed-Methods Analysis of Service Agent Empowerment and Customer Experience Outcomes - Anirudh Sharma Peri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article investigates the implementation and impact of Agent Force technology within the Salesforce ecosystem, examining its role in transforming customer service operations and agent empowerment. The article explores how AI-powered tools, centralized workspaces, and intelligent routing systems influence service delivery outcomes through a mixed-methods approach combining quantitative performance metrics and qualitative agent feedback. The article reveals significant improvements in agent productivity, case resolution efficiency, and customer satisfaction following Agent Force implementation. Integrating artificial intelligence and automated workflows substantially enhances decision-making capabilities and resource utilization. Furthermore, the article identifies critical success factors in change management and technology adoption, providing a comprehensive framework for organizations considering similar transformations. The findings contribute to the theoretical understanding of digital transformation in customer service and practical implementation strategies while highlighting the evolving relationship between technological advancement and human-centered service delivery in modern CRM systems. This article addresses a crucial gap in existing literature regarding the holistic impact of integrated service platforms on operational efficiency and employee empowerment in enterprise-scale customer service environments.